Comparison of the Effectiveness of Acceptance and Commitment Therapy and Emotion-Focused Therapy on the Burden of Caregivers of Individuals with Dementia - Pourmand, Zahra; Jahangir, Pantea; Rezakhani, Simindokht (Journal of Assessment and Research in Applied Counseling (JARAC), 2024)
Objective: The present study aimed to compare the effectiveness of Acceptance and Commitment Therapy (ACT) and Emotion-Focused Therapy (EFT) on the burden of caregivers of individuals with dementia.Methods and Materials: This research employed a quasi-experimental method with a pretest-posttest-follow-up design and a control group. The statistical population of this study was selected from the primary caregivers (wives and daughters) of individuals with dementia who visited the Iranian Dementia Association (located in Tehran) in 2023. From this population, 45 subjects were purposefully selected and randomly assigned to three equal groups of 15 (two experimental groups and one control group). To collect data, the Caregiver Burden Scale by Novak and Guest (1989) was utilized. Data were analyzed using SPSS software and multivariate analysis of covariance (MANCOVA) tests.Findings:  The results indicated that both ACT and EFT interventions had a significant effect on reducing the burden of caregivers of individuals with dementia in the post-test and follow-up phases compared to the control group.Conclusion:  The findings suggest that ACT had a greater impact on reducing the burden of caregivers of individuals with dementia compared to EFT.